Vanishing tumor in pregnancy - M V Vimal; Sweta Budyal; Rajeev Kasliwal; Varsha S Jagtap; Anurag R Lila; Tushar Bandgar; Padmavathy Menon; Nalini S Shah (Indian Journal of Endocrinology and Metabolism, 2012)
A patient with microprolactinoma, who had two successful pregnancies, is described for management issues. First pregnancy was uneventful. During the second pregnancy, the tumor enlarged to macroprolactinoma with headache and blurring of vision which was managed successfully with bromocriptine. Post delivery, complete disappearance of the tumor was documented.